Existência e Unicidade dos Números Reais via Cortes de Dedekind - Pontes, Kerly Monroe (2014)
This work aims to show the existence and Uniqueness of the field of Real Numbers, using for this, Dedekind' Cuts theorem and the Definition by Recursion.To fulfill his goal, we define the notion of Dedekind Cut and present some of its properties; then introduce the notions of Archimedean Ordered and Field, Complete Field Sorted and finally articulate and demonstrate the Uniqueness Theorem of Field Real Numbers.